Heat Transfer Coefficient Estimation of Falling Film for Horizontal Tube Multi-Effect Desalination Evaporator Using CFD - Furqan Tahir (14429547) (2021)
The multi effect desalination (MED) plant comprises of horizontal tube falling evaporators with the operational range of 40°C – 65°C, and can accommodate 8 – 10 evaporators/effects. The operating temperature range is limited by scale formation and condenser temperature. With the recent advances in antiscalants and vapor compression systems, the higher limit can be increased up to 85°C, and the lower limit can be reduced to 5°C. Therefore, more evaporators can be used to augment the amount of desalinated water, and the thermal performance of evaporators for a broader range needs to be assessed. In this study, the heat transfer coefficient at inlet temperatures of 85°C and 5°C, and different liquid loads, are numerically estimated. For this purpose, a two-dimensional CFD model is developed and validated. The computed results demonstrate that the heat transfer coefficient at the impact point is the highest that decreases with the angular position of the tube. The recirculations in the impingement zone enhance the heat transfer because of better mixing. At Ti = 85°C, the heat transfer performance is better due to lower film thickness, recirculations, and broad thermal developing region. For a liquid load of Γ1/2 = 0.09 kg/(m•s), the heat transfer coefficient at Ti = 85°C is 43.5 % higher as compared to that of at Ti = 5°C. Furthermore, the higher operating temperature limit should be increased instead of decreasing operating temperature for improved heat transfer performance. Other Information Published in: International Journal of Thermofluids License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ijft.2021.100101